(untitled) (Research, Society and Development, 2023)
Copaiba tree species are widely distributed in the Amazon and Midwest regions of Brazil. Its oil is used as an anti-inflammatory of the urinary tract, in pulmonary disorders, anti-ulcer, anti-asthmatic, expectorant, pneumonia, sinusitis, dysentery, urinary incontinence, cystitis and leukorrhea and as an antitumor. The objective of this work was to evaluate the antifungal activity of Copaifera reticulata Ducke oilresin and its nanoemulsion compared to the already known antifungal of synthetic origin itraconazole on the wild strain of Aspergillus Fumigatus Fresen. isolated from Bertholletia excelsa Bonpl. The fungitoxicity of both the oil and the nanoemulsion were determined by the Poison Food technique. Using Itraconazole (brand: Prati; Batch: 16A43N) at a concentration of 1.6 µg/mL, as a positive control and Tween 20 at a concentration of 1.6 µg/ml, as a negative control and the fungus in a culture medium without the oil, as a control. The treatments were carried out in triplicate and the mycelial growth record was evaluated every 24h, 48h and 72h, measuring the transversal and longitudinal diameters, for the analysis of the Mycelial Growth Inhibition Percentage (% PIC) and daily radial growth of the fungal colony. The experimental design was completely randomized, in a factorial scheme, 7 x 1 x 3 x 3 (concentrations x fungus x control x repetitions). It was verified that both the copaiba oilresin and its nanoemulsion are potential candidates in the control of A. fumigatus. Besides not being observed any type of resistance of A. fumigatus regarding the action of Itraconazole.